Predicting Financial Distress Amongst Public Listed Companies in Malaysia using Altman’s Z-Score Model and Auditors’ Opinion on Going Concern - Yee, Hun Leek (Curtin University, 2018)
The framework used in this study, to predict financial distress amongst the Public Listed Companies (PLCs) in Malaysia, utilizes the 5-variables Altman’s Z-Score Model as the base model and the Auditors’ Opinion on going concern as the 6th variable. Multiple Discriminant Analysis (MDA) and Logistic Regression Analysis (LRA) have been employed, and the revised 6-variables model developed using LRA has the highest accuracy to predict financial distress amongst the PLCs in Malaysia.